Galectin-3 Released by Pancreatic Ductal Adenocarcinoma Suppresses γδ T Cell Proliferation but Not Their Cytotoxicity - Gonnermann, Daniel; Oberg, Hans-Heinrich; Lettau, Marcus; Peipp, Matthias; Bauerschlag, Dirk; Sebens, Susanne; Kabelitz, Dieter; Wesch, Daniela (Frontiers in Immunology, 2020)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an immunosuppressive tumor microenvironment with a dense desmoplastic stroma. The expression of β-galactoside-binding protein galectin-3 is regarded as an intrinsic tumor escape mechanism for inhibition of tumor-infiltrating T cell function. In this study, we demonstrated that galectin-3 is expressed by PDAC and by γδ or αβ T cells but is only released in small amounts by either cell population. Interestingly, large amounts of galectin-3 were released during the co-culture of allogeneic in vitro expanded or allogeneic or autologous resting T cells with PDAC cells. By focusing on the co-culture of tumor cells and γδ T cells, we observed that knockdown of galectin-3 in tumor cells identified these cells as the source of secreted galectin-3. Galectin-3 released by tumor cells or addition of physiological concentrations of recombinant galectin-3 did neither further inhibit the impaired γδ T cell cytotoxicity against PDAC cells nor did it induce cell death of in vitro expanded γδ T cells. In initial proliferation of allogeneic or autologous resting peripheral blood and tumor-infiltrating Vδ2-expressing γδ T cells was impaired by galectin-3 in a cell-cell-contact dependent manner. The interaction of galectin-3 with α3β1 integrin expressed by Vδ2 γδ T cells was involved in the inhibition of γδ T cell proliferation. The addition of bispecific antibodies targeting γδ T cells to PDAC cells enhanced their cytotoxic activity independent of the galectin-3 release. These results are of high relevance in the context of an in vivo application of bispecific antibodies which can enhance cytotoxic activity of γδ T cells against tumor cells but probably not their proliferation when galectin-3 is present. In contrast, adoptive transfer of in vitro expanded γδ T cells together with bispecific antibodies will enhance γδ T cell cytotoxicity and overcomes the immunosuppressive function of galectin-3.